GNC strategies and flight results of Hayabusa2 first touchdown operation. (September 2020) - Ono, Go; Terui, Fuyuto; Ogawa, Naoko; Kikuchi, Shota; Mimasu, Yuya; Yoshikawa, Kent; Ikeda, Hitoshi; Takei, Yuto; Yasuda, Seiji; Matsushima, Kota; Masuda, Tetsuya; Saiki, Takanao; et al.
Abstract: Hayabusa2 is a Japanese sample return mission from the near-Earth asteroid Ryugu. The Hayabusa2 spacecraft was launched on December 3, 2014, and arrived at Ryugu on June 27, 2018. It stayed there until November 13, 2019 for in situ observation and soil sample collection, and will return to the Earth in November or December 2020. During the stay at the asteroid, the spacecraft performed a touchdown operation successfully for the first time in February 2019. Since the surface of Ryugu was rough and full of boulders, a targeted area finally found had a radius of only 3 m. There were several technical challenges to overcome including demanding guidance, navigation and control accuracy to realise the touchdown operation. In this paper, strategies and technical details of the guidance, navigation and control systems are presented. The flight results prove that the performance of the systems was satisfactory and largely contributed to the success of the operation. Highlights: Hayabusa2 is a Japanese sample return mission from the near Earth asteroid Ryugu. Hayabusa2 touched down to Ryugu successfully in February 2019. Ryugu's surface was rough; guidance, navigation and control accuracy were demanding. Guidance, navigation and control systems and strategies realised pinpoint touchdown. Flight results prove satisfactory performance and final position error of only 1 m.